Psychological Empowerment of Women through Micro-Enterprises Established in Parbat District, Nepal - Dhaubhadel, Sarita (Nepal Journal of Multidisciplinary Research, 2022)
One method of empowerment is a progressive one. Women's empowerment is essential to manage and alter traditional traditions in the modern setting. Governmental and non-governmental organizations are attempting to empower women holistically to eliminate gender-based prejudice from the process. One form of empowerment that might give people the confidence to play a significant role in society is psychological empowerment. The study aimed to determine how micro businesses gave women psychological power. In the Parbat district, 384 working women participated in the survey. Because the p-value was 0.000, which was less than 0.05 significant levels, the results showed a significant shift in the micro-enterprise between before (mean 15.6105) and after (mean 25.8421). It demonstrates the beneficial effects of micro-business on the psychological emancipation of women. Therefore, the government should keep up this policy to maintain success and give women more political clout.